Ecological health assessments of rivers with multiple dams based on the biological integrity of phytoplankton: A case study of North Creek of Jiulong River - Ling Lin (Elsevier, 2021)
North Creek of Jiulong River is characterized by large falls and a high degree of cascade-driven hydropower development. In this paper, ecological health assessments for North Creek of Jiulong River were carried out by a field survey of seasonal phytoplankton community structure dynamics and constructing an index system, the planktonic index of biotic integrity, P-IBI, to compare ecosystem health across different seasons. North Creek were relatively healthy in the summer and fall, but exhibited the worst conditions in the winter. With the exception of fall samples, the assessments for more than 50% of the sites in the dam reservoir area were lower than “moderate.” Further, the ecological health of the mainstream was lower than that of the tributaries. The P-IBI index across different seasons was correlated with some basic water physicochemical parameters (chlorophyll a, COD and DO concentrations). Importantly, these assessment results were consistent with actual water quality monitoring results, indicating that it is feasible to use P-IBI to evaluate river health status. The assessment of seasonal changes in algal community health is helpful for developing management strategies for rivers with multiple dams.